Analisis Perbandingan Penerapan Model PjBL (Project Based Learning) dengan PBL (Problem Based Learning) dalam Meningkatkan Hasil Belajar Peserta Didik pada Pembelajaran Fisika - Kurniawan, Diky; Sabaruddin, Sabaruddin (Intelektualita: Journal of Education Sciences and Teacher Training, 2023)
Nowadays, innovative learning models such as Project Basic Learning (PJBL) and Project Based Learning (PBL) are becoming increasingly popular, especially in the context of physical education. A qualitative study using document analysis was conducted to understand the differences in learning outcomes between the two models. The results showed that PJBL and PBL provided excellent learning outcomes for students with a high degree of accuracy. The comparison table between the Likert scale and the circle graph illustrates a continuous distribution of scores, reaching 50% for excellent learning outcomes. The conclusion of this study is that while both PPA and PBL are effective in improving student learning outcomes, they also have a positive impact on the education process in today's world